Rethinking liability of internet intermediaries in Malaysia: a comparative legal analysis with the European Union and the United States - Abdul Ghani Azmi, Ida Madieha; Alavi, Rokiah; Ismail, Suzi Fadhilah; Daud, Mahyuddin (2016)
Access to the Internet is faster and more reliable as Malaysia approaches Vision 2020. Government and private sectors have worked hard to improve necessary ICT access and infrastructures – as seen in this paper. More companies provide Internet access and become ‘Internet intermediaries’ . Some created digital content of their own while others merely hosts for a third party. Since Internet intermediaries are the gateway that connect Internet users to the digital world, they have become victims to legal actions for hosting third party illegal content. Generally, the law does not place any liability towards Internet intermediaries that acted as mere conduits. However, this alone does not guarantee that they will be immune from legal actions for hosting third party content. This paper analysed the legal position of Internet intermediaries in Malaysia on the issue of liability for hosting third party illegal content. The question here is - whether Malaysian Internet intermediaries are truly safe from legal liability for hosting third party illegal content. If the answer is in the negative, is there any hope for them? This paper compared legal positions stated in the famous EU E-Commerce Directive 2000 and the US Digital Millennium Copyright Act 1998 for the protections accorded to Internet intermediaries – and found rooms for improvement in the Malaysian laws. This paper is organised as follows. The first part outlined the development of Internet access and infrastructure in Malaysia that had led to the growth of Internet intermediaries. There exists insufficient safeguards to protect Internet intermediaries in Malaysia against third party liability. To address this issue, the second part analytically compared the Malaysia position with the European and United States safe harbour regimes. This paper concludes that relevant Malaysian laws on liability of Internet intermediaries require enhancement to safeguard Internet intermediaries against unnecessary third party legal actions.